2017
DOI: 10.25115/ejrep.v8i22.1426
|View full text |Cite
|
Sign up to set email alerts
|

Las TIC en las titulaciones universitarias de grado: análisis del conocimiento y uso en el alumnado de la Universidad a Distancia

Abstract: Las TIC en las titulaciones universitarias de grado: análisis del conocimiento y utilización en el alumnado de la universidad a distancia Resultados. Los resultados muestran diferencias estadisticamente significativas en el uso y conocimiento de las TIC, entre los grupos, observándose que la mayoría del alumnado no se sienten preparado para utilizar los recursos informáticos en sus estudios. Discusión y conclusiones.Los resultados principales del presente trabajo indicaron que el alumnado que estudia en la uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
1
0
3
Order By: Relevance
“…In particular, in the present study, it has been found distance students show more favorable attitudes towards the affective dimension, while the face-to-face students have more favorable attitudes in cognitive and behavioral aspects, as well as the total test; thus corroborating the conclusions provided by Suriá (2010), as well as the results found by Zhan & Mei (2013), Jaggars (2014) and Young & Duncan (2014). All these authors affirm that the affection is very important for distance students, because they lack the presence of classmates and teachers, which can result in isolation and less satisfaction in their learning.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, in the present study, it has been found distance students show more favorable attitudes towards the affective dimension, while the face-to-face students have more favorable attitudes in cognitive and behavioral aspects, as well as the total test; thus corroborating the conclusions provided by Suriá (2010), as well as the results found by Zhan & Mei (2013), Jaggars (2014) and Young & Duncan (2014). All these authors affirm that the affection is very important for distance students, because they lack the presence of classmates and teachers, which can result in isolation and less satisfaction in their learning.…”
Section: Discussionsupporting
confidence: 91%
“…Las TIC se han convertido en un pilar esencial para la docencia universitaria. En este sentido los universitarios, independientemente de su edad, consideran que necesitan aprender a manejar las TIC para tener éxito en su formación universitaria (Surià, 2010).…”
Section: Ventajas De La Incorporación De Las Tic Para El Aprendizaje unclassified
“…Therefore, the adaptation to the use of new technologies in the current context is undeniable and a methodological change is needed on the part of the teacher to incorporate the use of new technologies in the classroom [13].…”
Section: Introductionmentioning
confidence: 99%